2022
DOI: 10.3390/brainsci12111561
|View full text |Cite
|
Sign up to set email alerts
|

A Characterization of Brain Area Activation in Orienteers with Different Map-Recognition Memory Ability Task Levels—Based on fNIRS Evidence

Abstract: Background: Mapping memory ability is highly correlated with an orienteer’s level, and spatial memory tasks of different difficulties can reveal the spatial cognitive characteristics of high-level athletes. Methods: An “expert–novice” experimental paradigm was used to monitor behavioral performance and changes in cerebral blood oxygen concentration in orienteering athletes with tasks of different difficulty and cognitive load using functional near-infrared spectroscopic imaging (fNIRS). Results: (1) there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This heightened focus, coupled with task difficulty, contributed to enhanced blood oxygen concentration 53 . Studies investigating spatial perception also revealed that activation of the left VLPFC was significantly higher in novices compared to experts in real-world scenarios 54 .…”
Section: Fnirs Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This heightened focus, coupled with task difficulty, contributed to enhanced blood oxygen concentration 53 . Studies investigating spatial perception also revealed that activation of the left VLPFC was significantly higher in novices compared to experts in real-world scenarios 54 .…”
Section: Fnirs Resultsmentioning
confidence: 99%
“…Therefore, both spatial memory and mental rotation are a kind of cognitive ability 19 . Relevant studies have pointed out that expert orienteering athletes show a certain advantage in spatial memory ability in specialized scenarios 20,21 , caused by the reasons mainly stemming from the perennial sports experience and specialized training 22 . It has also been pointed out that orienteering athletes' mental rotation ability constrains the efficiency of map literacy, and that sports experience can influence the development of cognitive abilities by changing the structure and function of the brain 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of novices and experts was significantly higher in the fundamentals of training tasks than in tasks in the knee module (if the effect size, d > 0.8, then significant with p < 0.05). This suggests that both groups had focused on most of the tasks, especially the RDLPFC area, which is reported to be associated with spatial navigation tasks [22, 33].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, both spatial memory and mental rotation are a kind of cognitive ability 19 . Relevant studies have pointed out that expert orienteering athletes show a certain advantage in spatial memory ability in specialized scenarios 20 , 21 , caused by the reasons mainly stemming from the perennial sports experience and specialized training 22 . It has also been pointed out that orienteering athletes’ mental rotation ability constrains the efficiency of map literacy, and that sports experience can influence the development of cognitive abilities by changing the structure and function of the brain 16 .…”
Section: Introductionmentioning
confidence: 99%